Research on the Effects of International R&D on Carbon Productivity in China: Empirical Study Based on Dynamic Panel - Dawei Gao; Haisong Nie; Marina Takeyasu (International Journal of Agriculture System, 2018)
At present, nearly 70% of the world's new increase carbon dioxide emission comes from China. Technology is the key power to develop low-carbon economy. Because of the shortage of independent　R & D and the relative backwardness of low-carbon technology,　Chinese need developed countries’ R&D capital and advanced technology to promote low-carbon technologies. Based on the panel data from Chinese 30 provinces from 2001 to 2014 and dynamic panel model, this paper researchs on the effects of international R&D on regional carbon productivity in China. The empirical results show that, the technology spillover effect of FDI and import trade can improve carbon productivity, and imported technology contracts play a positive role on carbon productivity, but not significant. There is a significant positive correlation between independent R&D and carbon productivity. Finally, the corresponding policy is put forward according to the conclusions